Etnoconhecimento e variabilidade morfológica de castanha-do-brasil (Berthollethia excelsa Bonpl.: Lecythidaceae) em área da Amazônia matogrossense - Camargo, Flora Ferreira (2011)
This study aimed to expand knowledge about the genetic and morfhological variability of the Brazil-nut. Adding to this its purpose is to gather information about the ethnic knowledge related to this species. The first chapter presents information on various aspects of the ecology of this species and its characterization, proposing measures for the preservation of germplasm and rational use of an important genetic resource for the people of the Amazon region. They gathered evidence in the literature about the hypothesis of anthropogenic Amazonian landscape and through this review contribute to the study of the dispersal of Brazil-nut trees on the plains of this region. The study also sought an investigation of empirical data on the relationship of the Brazil-nut with human populations their uses in everyday life, beliefs and considerations. These data turn out to emphasize the collaboration of popular knowledge as an instrument to identify the genetic variability within populations of the Brazil-nut, a variability that has been found through developing ethnosciences. We identified three types of B. excelsa; Rosa, Gust and Mirim to seek direct management decisions and increased production and conservation of the species. The etnoclassification was considered important for management of the trees, encouraged by the decision of the choice of germoplasm in breeding programs and conservation genetics, especially for strategies aimed at the enrichment of native population and uses in agroferestry.The values found in the estimation of parameters and genetic gain in pre-breeding of specie.in the Cotriguaçu municipality of northwestern Mato Grosso, were significant for matrices of the rosa encouraging the use of germplasm.